2022
DOI: 10.3390/biomedicines10061227
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Associated Mucosal Immune Response in Eosinophilic Granulomatosis with Polyangiitis (EGPA)

Abstract: Eosinophilic granulomatosis with polyangiitis (EGPA) is an anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis. A genome-wide association study showed a correlation between ANCA-negative EGPA and variants of genes encoding proteins with intestinal barrier functions, suggesting that modifications of the mucosal layer and consequent gut dysbiosis might be involved in EGPA pathogenesis. Here, we characterized the gut microbiota (GM) composition and the intestinal immune response in a cohort of EGPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Notably, an enrichment of potential pathobionts (Enterobacteriacee and Streptococcaceae) was found in Eosinophilic Granulomatosis with Polyangiitis ( 23 )., particularly in patients with active disease, while lower levels were found in patients on immunosuppression, compared with non-immunosuppressed ones. Significantly lower amounts of hexanoic acid were found in patients, compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, an enrichment of potential pathobionts (Enterobacteriacee and Streptococcaceae) was found in Eosinophilic Granulomatosis with Polyangiitis ( 23 )., particularly in patients with active disease, while lower levels were found in patients on immunosuppression, compared with non-immunosuppressed ones. Significantly lower amounts of hexanoic acid were found in patients, compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated an association between occupational exposures to organic solvents, silica, and farming and the risk of EGPA [22], while tobacco exposure resulted protective particularly in ANCA-negative EGPA, by suppressing the immune system at mucosal level. The role of mucosal disfunction in EGPA is also supported by the evidence of an imbalance in gut mucosal immune response secondary to an enrichment of intestinal pathobionts [23].…”
Section: Eosinophilic Granulomatosis With Polyangiitis Pathophysiologymentioning
confidence: 89%
“…Recent research is now suggesting the existence of a two-way association between microbiota and the variability of many human traits. Indeed, dysbiosis—defined as an imbalance in microbiota profiles—has been associated with a range of complex diseases, including metabolic, immune, neurodegenerative, and neurological diseases [ 8 , 9 , 10 , 11 ]. Nonetheless, the underlying mechanisms of the reciprocal influence among individual or communities of microorganisms and human health are puzzling and need to be further clarified.…”
mentioning
confidence: 99%